Seismic performance of moment frames under multiple fling-step pulse ground motions - Ade Faisal; Bambang Hadibroto; Ahmad Fahmy Kamarudin; Afiful Anshari (SINERGI, 2022)
The displacement fling-step pulse seldom signatures near-field earthquake in its ground motions. It is well recognized that the near-field ground motion with velocity pulse amplifies the building drift larger than the regular ground motion. Recent findings explain that the building experiences minor damage to collapse is not caused only by the single earthquakes, which in many cases are due to repeated ground motion. The seismic performance of moment frames under the displacement fling-step pulse motion is not studied, particularly when this type of motion applies. Thousands of nonlinear inelastic response history analyses are conducted in order to find out the inter-story drifts, as the engineering demand parameter throughout the incremental dynamic analysis, on the 5 to 20-story moment resisting frames under the influence of multiple ground motions with a fling-step pulse. The special, intermediate, and ordinary types of moment frames are considered, respectively. On average, the evaluation result explains that the intensity measure of multiple ground motions with a fling-step pulse needs 68.37% lower than the single ground motion in order to produce the near collapse inter-story drift. This means the multiple ground motion with fling step pulse increases the probability of near collapse of frames significantly.